Graphene Q-switched Tm:KY(WO4)2 waveguide laser. (14th February 2017) - Kifle, E; Mateos, X; Loiko, P; Yumashev, K; Yasukevich, A; Petrov, V; Griebner, U; Aguiló, M; Díaz, F
Abstract: We report on the first Tm 3+ -doped double tungstate waveguide laser passively Q-switched by a graphene saturable absorber using a 12.4 µ m-thick 3 at.% Tm:KY0.58 Gd0.22 Lu0.17 (WO4 )2 epitaxial layer grown on a (0 1 0)-oriented pure KY(WO4 )2 substrate. This laser generated 5.8 nJ/195 ns pulses at 1831.8 nm corresponding to a pulse repetition frequency of 1.13 MHz. These are the shortest pulses achieved in passively Q-switched Tm waveguide lasers. The laser slope efficiency was 9% and the Q-switching conversion efficiency reached 45%. Graphene is promising for the generation of ns pulses at 2 µ m in Tm 3+ -doped double tungstate waveguide lasers operating in the MHz-range.